2013
DOI: 10.1016/j.engfracmech.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic approach to the Kitagawa–Takahashi diagram using a multiaxial probabilistic framework

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. AbstractThe aim of this paper is to propose a flexible multiaxial modelling framework that is capable of combining two fatigue damage mechanisms so as to continuously describe the KitagawaTakahashi diagram. It is proposed that this diagram represents two distinct fatigue damage mechanisms: one associated with crack initiation (or microstructurally small cracks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…describing the dependence of ∆K th or limit stress ∆σ w on defect size [11]. Among the various possibilities adopted in the literature, the simplest approach is modelling the defect size according to the √ area parameter and adopting the modified El-Haddad formulation 25 [4,14,[53][54][55] where:…”
Section: Model For Fatigue Strengthmentioning
confidence: 99%
“…describing the dependence of ∆K th or limit stress ∆σ w on defect size [11]. Among the various possibilities adopted in the literature, the simplest approach is modelling the defect size according to the √ area parameter and adopting the modified El-Haddad formulation 25 [4,14,[53][54][55] where:…”
Section: Model For Fatigue Strengthmentioning
confidence: 99%
“…This type of diagrams could be very useful for the design of heat treated components with variable hardness. It should be noted that in this work only tensile and shear loads have been investigated, however it is possible to generalise the approach for combined tension-torsion loads using a expression for the stress intensity factor that is suitable for more complex loads [25].…”
Section: Application Using the Papadopoulos And Lefm Criteria Combinamentioning
confidence: 99%
“…Pessard et al [25,26] in order to model the effect of the heat treatment and the presence of defects on the fatigue behaviour of the 22MnB5 steel. The principal hypothesis of this criterion is that two different fatigue damage mechanisms coexist (i.e.…”
Section: A Probabilistic Multiaxial Fatigue Criterion and A Kitagawa mentioning
confidence: 99%
“…Naderi et al [26] investigated the effects of finite element types and sizes, initial flaws and material property variations on the fatigue life scatter of metals, and predicted the plastically induced fatigue damage for four types of metals. Pessard et al [51] developed a probabilistic multiaxial modelling framework to describe the Kitagawa-Takahashi diagram by combining two fatigue damage mechanisms, which is based on the weakest link hypothesis. Recent research in [38] demonstrated that current safe-life design methods [12]- [14], [52], [53] introduced a series of partial safety factors to empirically or semi-empirically consider the variability in applied stress and material behavior.…”
Section: Introductionmentioning
confidence: 99%